Pengamatan strategi pemasaran untuk meningkatkan daya saing koperasi dan UMKM - Nabila A, Berliana Afshochun (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the marketing strategies implemented by cooperatives and SMEs in Indonesia and their impact on competitiveness. Using descriptive qualitative methods with interviews, surveys, and document analysis, the study found that the application of the 4P concept (Product, Price, Place, Promotion) is crucial. Adjusting products to market needs, setting competitive prices, effective distribution, and the use of social media and digital marketing increase product visibility and customer interaction. SWOT analysis shows strengths such as high-quality products and competitive prices but also weaknesses in capital and digital marketing knowledge. There are opportunities from the digital market and government support, but competition and economic instability remain threats. In conclusion, effective marketing strategies can enhance the competitiveness of cooperatives and SMEs by expanding market share, increasing customer satisfaction, and loyalty. Cooperatives and SMEs need to continually innovate, evaluate pricing strategies, diversify distribution channels, utilize digital technology, and regularly analyze the market to adjust strategies to the latest trends.